Employment and Happiness of the Older People in Romania and the Visegrád Countries: Analysis of the European Quality of Life Surveys - Berde Éva (Studia Universitatis Vasile Goldis Arad, Seria Stiinte Economice, 2021)
We used the last three waves of the European Quality of Life Surveys to analyze the happiness of older workers in Romania and the Visegrád countries. Applying ordinary least squares and ordered logit models we showed that being employed makes people happier ceteris paribus than being unemployed. This effect is the same for younger and older persons in the V4 countries, but there is an extra positive effect for older workers in Romania.